Socio-Psychological Factors as Determinants to Information-Seeking Behavior of LIS Undergraduates in Kwara State - Kabir Alabi Sulaiman (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2020)
This study examines socio-psychological factors as determinants to information-seeking behaviour of LIS undergraduates in Kwara state. A descriptive survey method was adopted. A questionnaire was used to collect data for the study. The total population for the study is 2392. From which the sample size of 333 was selected using Raosoft size calculator. The study revealed that most of LIS undergraduate have fear during information searching process. The study also revealed that LIS undergraduates are of opinions that having access to the internet improves their ability to search for information. It was also found out that most of LIS undergraduates were helped with internet to have access to various sources of information simultaneously. In conclusion, there is a significant relationship between computer/internet and information-seeking behaviour of LIS undergraduates in Kwara state. This research recommends that LIS undergraduate should improve confidence in the use of internet/computer to seek information with ease and LIS undergraduate should develop a mechanism for self-confidence while seeking for information